Assessing ecological impacts of agricultural practices using frogs as bioindicators - AGUNG SIH KURNIANTO; ATI KUSUMAWATI; LENNY WIDJAYANTHI; DISTIANA WULANJARI; INDAH IBANAH; MUHAMMAD ARDIAN ARSY MAJID; DEA AYU PUSPITASARI; BAGUS PRIAMBODO (Society for Indonesian Biodiversity, 2024)
Abstract. Kurnianto AS, Kusumawati A, Widjayanthi L, Wulanjari D, Ibanah I, Majid MAA, Puspitasari DA, Priambodo B. 2024. Assessing ecological impacts of agricultural practices using frogs as bioindicators. Biodiversitas 25: 3208-3215. The rapid intensification of agriculture, driven by the increasing global demand for food, heavily relies on chemical inputs like pesticides and synthetic fertilizers. While these practices enhance production, they pose significant challenges to ecological balance and environmental health. Biomonitoring efforts have been developed to detect and evaluate the chemical pollutants' impact on the environment, employing species like the rice field frog (Fejervarya limnocharis Gravenhorst 1829) as bioindicators. This study aimed to assess the reliability of rice field frogs' liver gravimetry and morphology as biomonitoring tools using various analytical methods. Samples were collected from rice fields managed both organically and conventionally to analyze liver weight, individual weight, and Snout-Vent Length (SVL). This analysis was conducted to understand the environmental effects on these physiological parameters. Statistical analysis revealed significant differences between the two management practices, indicating environmental conditions notably influence the frogs' physiological parameters, highlighting their potential as bioindicators for chemical pollutants. The findings underscore the need for further research to optimize biomonitoring methods for sustaining environmental health and agricultural practices. This study contributes to the development of more sophisticated and effective biomonitoring methods, supporting sustainable agricultural practices and environmental mitigation strategies.